Steps to a Planning Oriented Towards Territorializing Immanence - Luciano De Bonis (In_Bo, 2023)
The essay tries to provide a contribution in the direction of a planning that is more responsive to the potential of community self-government of places, focusing in particular on some issues considered fundamental to this end, namely: the possibility of rethinking democracy as demo-dynamic; the relationship between the political sphere and the urban sphere in some political visions inspired by community self-determination; a geo-historical interpretation of the origin and evolution of the city, up to the current forms of regional urbanisation; a vision of the urban finally freed from the classic city/countryside dualism, as well as from other correlated dualisms; the need for planning to renounce any type of transcendent rationality to favour forms of territorial self- determination. On the basis of the acquisitions now matured in some interpretative strands of the aforementioned questions, a form of planning is proposed which, in order to move towards territorializing immanence, is based on the recognition of the distinction between the common good (and commoning processes) and the private or public ones, placing moreover itself within the framework of a circularly subsidiary approach which, even within the given institutional framework, tends to make the most of the self- regulation faculties, and of self-planning, already available to local communities.